What Constrains Indian Manufacturing? - Poonam Gupta; Rana Hasan; Utsav Kumar (Asian Development Bank (ADB), 2008)
India has undertaken extensive reforms in its manufacturing sector in the last two decades. However, an acceleration of growth in manufacturing, and a concomitant increase in employment, has eluded India. What might be holding the sector back? Using Annual Survey of Industries data at the 3-digit level, and difference in differences estimates, this paper finds that the postreform performance of the manufacturing sector is heterogeneous across industries. In particular, industries that were dependent on infrastructure or external finance and were labor-intensive have not been able to reap the maximum benefits of reforms. The results point to the importance of infrastructure development and financial sector development for the manufacturing sector's growth to accelerate further. They also emphasize the need to clearly identify and address the factors inhibiting the growth of labor-intensive industries.
hdl:11540/1775
Keywords: 330; Industrie; Infrastruktur; Finanzsektor; Arbeitsintensität; Indien